Role of serum amyloid A in atherosclerosis. Issue 4 (August 2019) - Shridas, Preetha; Tannock, Lisa R.
Abstract : Purpose of review: Acute phase serum amyloid A (SAA) is persistently elevated in chronic inflammatory conditions, and elevated levels predict cardiovascular risk in humans. More recently, murine studies have demonstrated that over-expression of SAA increases and deficiency/suppression of SAA attenuates atherosclerosis. Thus, beyond being a biomarker, SAA appears to play a causal role in atherogenesis. The purpose of this review is to summarize the data supporting SAA as a key player in atherosclerosis development. Recent findings: A number of pro-inflammatory and pro-atherogenic activities have been ascribed to SAA. However, the literature is conflicted, as recombinant SAA, and/or lipid-free SAA, used in many of the earlier studies, do not reflect the activity of native human or murine SAA, which exists largely lipid-associated. Recent literatures demonstrate that SAA activates the NLRP3 inflammasome, alters vascular function, affects HDL function, and increases thrombosis. Importantly, SAA activity appears to be regulated by its lipid association, and HDL may serve to sequester and limit SAA activity. Summary: SAA has many pro-inflammatory and pro-atherogenic activities, is clearly demonstrated to affect atherosclerosis development, and may be a candidate target for clinical trials in cardiovascular diseases.